United States policy and nuclear non-proliferation: a preliminary comparison of the Bush and Obama administrations' approaches - Nel, Coligny (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Political Science))--University of Stellenbosch, 2010.